COVID-19 VACCINATION AND INCOME OF ONLINE DRIVERS IN BANDA ACEH - Mhd. Yafishan Novinda; Nanda Rahmi; Rustam Effendi (Fakultas Ekonomi dan Bisnis UNSYIAH, 2022)
Abstract The objective of the research is to examine empirically the differences in the income of online drivers for Gojek and Grab in Banda Aceh when before and after the vaccination period and the effect of the Covid-19 Vaccination in the income of online drivers in Banda Aceh. The total of research samples are 150 which is a combination of Gojek and Grab drivers using simple random sampling. This research uses a different test or t-test method through the Kolmogorov-Smirnov test and paired samples t-test model. Results of this study indicate that there are significant differences in the income of online drivers at before and after vaccination period, income increased significantly at after vaccination period and determinants of indicators have a significant positive effect in the income changes of online drivers.Keywords: Income, Vaccination, Covid-19, Online Driver